Psychopharmacology of anxiety disorders - Leonard, Brian (Henry Stewart Talks, 2007)
GABAergic pathways in normal brain, Drugs used in the treatment of anxiety disorders, Drugs that modulate the GABA receptor, Anxiolytics and benzodiazepine receptor, Noradrenergic pathways in generalized anxiety disorder (GAD)